Discourse analysis of male and female identity construction in fotonovelas of Corin Tellado - Amaya, Marcela (Universidad de Chile. Programa Domeyko, 2011)
This research in centered on the analysis discursive of the construction of the femenine and masculine identity on two Corin Tellado`s photonovels. Being the principal objetive to identify the production and reproduction on the speech of the stereotypes of the period. Following the expositions of Van Dijk, it´s understood by discursive reproduction of the denomination "(...) a preferential access to the text and the context, they take as base or resourse of power, comparable to social resourse (...)" (van Dijk 1997b:19). The results show how they express, represent and the forms on inequality are legetimized in the speech between generes proper of the patriarcal commanding system in the above mentiones period.